Development and content validation of the Satisfaction and Experience Questionnaire for Granulocyte Colony-Stimulating Factor (SEQ-G-CSF) - Aylin Yucel; Anne Skalicky; Olabimpe Ruth Eseyin; Emre Yucel; Rajesh Belani; Mark Bensink (SpringerOpen, 2021)
Abstract Background Several options for granulocyte colony-stimulating factor (G-CSF) prophylaxis of chemotherapy-induced febrile neutropenia are available to patients worldwide. We have developed a novel patient-reported outcome measure, the Satisfaction and Experience Questionnaire for G-CSF (SEQ-G-CSF), to help understand patients' perspectives of and satisfaction with different G-CSF options. Results Three oncology nurses and 40 adult oncology patients in the United States were enrolled and participated in focus group discussions to develop and refine the SEQ-G-CSF. Nurses had ≥ 5 years of experience treating oncology patients and were currently involved in the management of oncology patients receiving G-CSF prophylaxis. The patients had breast cancer, lung cancer, non-Hodgkin lymphoma, or prostate cancer (10 patients in each group) and were receiving G-CSF prophylaxis via injection or the on-body injector (OBI) device. The preliminary SEQ-G-CSF contained an item relevance questionnaire and three SEQ modules (sociodemographic, medical history, and G-CSF-related healthcare characteristics questionnaires). Twenty-one patients (53% of total sample size) discussed their experience and satisfaction with G-CSF. Their most common experiences were G-CSF effectiveness, convenience and benefits of the OBI, and relationships with healthcare providers. Side effects and having to undergo additional treatment were also reported. Satisfaction with aspects of G-CSF included the OBI and effectiveness of G-CSF treatment; dissatisfaction included inconvenience (having to return to the clinic the next day and administration of the injection) and the insurance approval process. The SEQ-G-CSF was finalized after three rounds of cognitive interviews and includes five domains related to general satisfaction (one item), treatment burden (four items), travel burden (two items), time burden (four items), and treatment compliance (two items). Conclusions The SEQ-G-CSF is a novel instrument that quantifies a patient's experience and satisfaction with different G-CSF options using 13 easy-to-understand items. This study provides evidence for the content validity of SEQ-G-CSF. Although further psychometric testing is required, the SEQ-G-CSF may be a useful addition to clinical trials, observational studies, and clinical practice.